Determination of robust material qualities and processing conditions for laser sintering of polyamide 12. Issue 7 (24th July 2013) - Wegner, Andreas; Mielicki, Christoph; Grimm, Tobias; Gronhoff, Burkhard; Witt, Gerd; Wortberg, Johannes
<x xml:space="preserve">Abstract</x> Material aging of Polyamide 12 (Laurinlactam) is a very common problem in laser sintering (LS). For stable process conditions, recycled material used in previous processes should be refreshed with 30–50% virgin powder material. However, even by following these refreshing strategies, material quality drops to an insufficient level after several process cycles which leads to poor part quality showing orange peel or poor mechanical properties when processed. In order to avoid this, a quality assurance system has been established to provide recommendations for robust process conditions and material qualities. A detailed study on aging processes in LS comparing two different machines was performed in order to analyze correlations between material quality, process parameters and part properties. Energy input allowing for robust processing conditions should be in a range between 0.325 and 0.42 J/mm3 showing almost identical values for both machines. Optimal material quality ranges was found to be machine specific, while the lower limit lies between 20 and 25 cm3/ 10 min for both machines used. Additionally, material aging characteristics in an oven and a LS machine were compared, in order to simulate material aging in the LS process by simple experiments in an oven. POLYM. ENG. SCI., 54:1540–1554, 2014. © 2013 Society of Plastics Engineers